2022
DOI: 10.3390/nu14142973
|View full text |Cite
|
Sign up to set email alerts
|

Spore Powder of Paecilomyces hepiali Shapes Gut Microbiota to Relieve Exercise-Induced Fatigue in Mice

Abstract: Paecilomyces hepiali, a fungal strain isolated from natural Ophiocordyceps sinensis, contains similar pharmacologically active components, has been used widely as a substitute of O. sinensis in functional food and medicine. However, the components and anti-fatigue effects of P.hepiali spores and their mechanisms of action are largely unknown. Here, we compared the chemical composition in P.hepiali spore (HPS) and mycelium (HPM) by liquid chromatography with tandem mass spectrometry analysis. We found 85 metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Guan et al. (2022) reported that Paecilomyces hepiali spore supplementation could increase the proportion of fecal Alistipes and alleviate fatigue in KM mice. However, another study has shown that the proportion of intestinal Alistipes is upregulated in individuals with CFS (Fremont et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guan et al. (2022) reported that Paecilomyces hepiali spore supplementation could increase the proportion of fecal Alistipes and alleviate fatigue in KM mice. However, another study has shown that the proportion of intestinal Alistipes is upregulated in individuals with CFS (Fremont et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Under varying pathological conditions, the Bacteroidetes genus Alistipes exhibits a range of effects, which can often be diverse and even contradictory. Guan et al (2022) reported that Paecilomyces hepiali spore supplementation could increase the proportion of fecal Alistipes and alleviate fatigue in KM mice. However, another study has shown that the proportion of intestinal Alistipes is upregulated in individuals with CFS (Fremont et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impairment of intestinal integrity is another extremely important effect of fatigue development [ 109 ]. Long-term exhaustive swimming exercise resulted in an increased abundance of Acetatifactor , Allobaculum , Oscillibacter , Paraprevotella , and Roseburia and a decreased abundance of Alistips , Clostridium , Akkermansia , Olsenella , and Lactobacillus in mice [ 122 ]. The analysis results showed that the beneficial bacteria ( Lactobacillus , Akkermansia , etc.)…”
Section: Polysaccharides Ameliorate Fatigue Via the Gut-muscle Axismentioning
confidence: 99%
“…The gut microorganism plays a fundamental role in modulating muscle adaptation to extensive training [ 105 ]. Increased probiotics in the gut can restore imbalances in the intestinal ecosystem, normalize serum biomarkers, and reduce intestinal inflammation, thereby relieving fatigue and enhancing exercise function [ 122 ]. Exercise training is beneficial to intestinal health, suggesting that exercise can regulate the composition of the microbial community and increase its biodiversity [ 24 , 131 ].…”
Section: Polysaccharides Ameliorate Fatigue Via the Gut-muscle Axismentioning
confidence: 99%